Silence as a sequel of the Peruvian internal war - Iguíñiz Echeverría, Javier Mª. (2006)
The internal war that took place in Peru for two decades brought silence as one of its consequences. In this article we try to classify silence or aspects of silence. This classification, based on the experiences described in the Report of the Truth and Reconciliation Commission (CVR, 2003), distinguishes an instrumental silence or silence for; a silence caused by the terrible events that took place or silence from; a silence resulting from the absence of important relations for an intimate communication, like relatives or friends, or silence with; and finally, a more profound silence, less describable, more personal but less manageable, simply a silence.